If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-3x + 4) = -6x + -4x + 8 Reorder the terms: 6(4 + -3x) = -6x + -4x + 8 (4 * 6 + -3x * 6) = -6x + -4x + 8 (24 + -18x) = -6x + -4x + 8 Reorder the terms: 24 + -18x = 8 + -6x + -4x Combine like terms: -6x + -4x = -10x 24 + -18x = 8 + -10x Solving 24 + -18x = 8 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 24 + -18x + 10x = 8 + -10x + 10x Combine like terms: -18x + 10x = -8x 24 + -8x = 8 + -10x + 10x Combine like terms: -10x + 10x = 0 24 + -8x = 8 + 0 24 + -8x = 8 Add '-24' to each side of the equation. 24 + -24 + -8x = 8 + -24 Combine like terms: 24 + -24 = 0 0 + -8x = 8 + -24 -8x = 8 + -24 Combine like terms: 8 + -24 = -16 -8x = -16 Divide each side by '-8'. x = 2 Simplifying x = 2
| -7=(-5) | | 4/21=h/27 | | 8b+6=ln(2c)+ln(c) | | 5(3g+1)=4(3g-1) | | 3x-x+8+5x-2= | | 4(3x-6)=2(4x+8) | | x^2-17x+c=0 | | 9x+2-11+3x=-x-4+13x-5 | | cos^2x=0 | | 10-2x+7x=40 | | 180=y+25+x | | 3(4x+3)=11x-7x-7 | | -65=5--30p-56p--16 | | 4x=2x-(3x-20) | | 2x-4(x-2)=-6+3x-26 | | 2x=12x-(7x-15) | | C=1.90+1.40t | | 20m+4m=14m-10 | | 289-5s=5 | | 2lnx-2=3 | | 4(-2+5)=-4x+4 | | 2(c+4)+3c=5(2c+10) | | -(18x-21)=7x-29 | | 6n+6=35 | | 20x-10=-2x+6x-26 | | 6r-24+r+30-7r= | | 4.26x-29.4=-3.5x | | 2/2-i=0 | | 5-9w-7= | | 3(x-3)-2(x+1)=5 | | x-2e^2*x=0 | | 3x=85 |